Value Added Tax (VAT) compliance through use of Electronic Fiscal Device (EFD) in Tanzania : A case study of Musoma district in Mara - Gwimile, Shaibu Rahibu (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance (MSc. A&F) of Mzumbe University